The role of Christian hospitality in addressing violence, strengthening tolerance, and deepening dialogue - Saragih, Jon Renis (Hanifiya: Jurnal Studi Agama-Agama, 2025)
This article explores the transformative role of Christian hospitality in addressing religious violence, strengthening interreligious tolerance, and deepening dialogical engagement in plural societies. Using a qualitative and literature-based approach, the study draws upon biblical exegesis and contemporary philosophical thought, particularly from Derrida, Levinas, and Zizioulas, to frame hospitality not merely as a moral virtue but as a radical theological praxis. The findings show that hospitality, in its unconditional form, dismantles the boundaries that sustain violence by welcoming the stranger as a sacred presence, including those once perceived as enemies. Unlike passive tolerance which often reinforces hierarchical relations, hospitality fosters active encounters rooted in mutual respect and shared humanity. Furthermore, the study demonstrates that dialog grounded in hospitality surpasses pluralistic formalism by offering a genuine relational space where differences are neither denied nor diluted, but embraced as sources of mutual growth. This dialogical hospitality challenges the binary between particularism and relativism, positioning openness to the other as a sacred imperative of faith. The study concludes that Christian hospitality holds profound potential as an interreligious ethical framework that transcends theological abstraction and responds concretely to the social fractures of post-secular societies. As such, this research contributes to the broader discourse on interfaith ethics, offering a nuanced paradigm for theological engagement, conflict resolution, and civic reconciliation across religious and cultural boundaries.